Phylogenetic Analysis of Streptomyces spp. Isolated from Soil Samples in Sulaimani Governorate - Syamand A. Qadir; Miran H. Qadir; Osama H. Shareef; Aryan M. Faraj (Polytechnic Journal)
Streptomyces species have been an important source of bioactive secondary metabolites and clinically useful for antibiotic production, including fosfomycin, daptomycin, oxytetracycline, streptomycin, and chloramphenicol. The main objective of this study was to isolate actinomycetes, especially Streptomyces from 8 soil samples that collected from two different places, which are districts in Sulaimani governorate, Kurdistan Region of Iraq. Totally, 30 diagnostic tests were carried out for representative of isolated Streptomyces depending on the color groups. The 16Sr DNA gene was sequenced, for ten isolated test strains were amplified with 2 universal primers after extraction of genomic DNA, only 8 of them were successfully sequenced. Phylogenetic analysis of 8 test strains carried out using base sequences of 16Sr DNA genes in the core genome. Four of isolated test strains were identified as a Streptomyces fulvissimus, and others were nominated as a Streptomyces anulatus. The obtained sequence data were compared with the sequence data of the closest related species in the international databases using EzTaxon Server program and (%) similarities were determined. Finally, phylogenetic analysis indicated that isolated test strains were nominated as (H001, H002, H003, and H004), which recognized members of the S. anulatus and the similarity with their type strain is 99.93%. Whereas, other four isolated test strains, including D001, D002, D003, and D004 recognized as members of the S. fulvissimus and similarity with their type strain is 100%.